UJI AKTIVITAS ANTIOKSIDAN TERONG BELANDA (SOLANUM BETACEUM CAV.) DENGAN METODE FRAP - Syarif, Sukmawati; Kosman, Rachmat; Inayah, Nurul (Jurnal Ilmiah As-Syifaa, 2015)
Test Antioxidant Activity of Dutch eggplant (Solanum betaceum Cav.) with FRAP method. This study aims to measure and determine the antioxidant activity Dutch eggplant (Solanum betceum Cav.) with FRAP method. Dutch eggplant was analyzed qualitatively by using the metod FRAP with FRAP reagent. Quantitatively mix with the sample solution was analyzed by FRAP method Uv-Vis spectrophotometer at a wavelength 596 nm. By using trolox as a reference standard. The results obtained in this research that Dutch eggplant has antioxidant activity with an total value of antioxidant activity, 0,9353 µmol Trolox/gr sample.